Physical therapy and its benefits in the postoperative period of mastectomized patients: an integrative literature review - Silva, Antônio Rogério da (2022)
Breast cancer is a public health problem because it has high incidence and mortality rates. The objective of this paper is to evaluate the effects of physical therapy in the post-surgical recovery process of mastectomized women, aiming to understand how the contributions of the physical therapist can improve the patient's living conditions. This is a study characterized by an integrated literature review (IRL) that can identify, synthesize, and conduct an extensive review on a specific topic. Full articles available in PubMed, Cochrane Library, BVS and PEDro databases, with publication time between 2016 and 2021, were considered eligible. By the analysis of the references presented, it can be observed that physical therapy in the process of recovery and rehabilitation in the post-surgical period of mastectomized women, showed significant results taking as a parameter the improvement in quality of life and complications of lymphedema, through appropriate physical therapy treatment. However, more studies are necessary, due to the complexity of the subject and the importance of talking about breast cancer and how it directly affects the physical and emotional state of a patient.